"Off the beaten map": Navigating with digital maps on moorland. Issue 1 (30th September 2019) - Smith, Thomas Aneurin; Laurier, Eric; Reeves, Stuart; Dunkley, Ria Ann
Abstract : Resources made available through the digital map app change, but do not replace, the skills of "ordinary wayfinding." Looking at the challenges of wayfinding with new mobile devices helps inform the development of digital mapping tools for navigating through difficult terrain. With this background in mind, in this paper we consider how the contemporary navigational resources of mobile devices with GPS, and the resources of countryside landscape features, are brought together in visiting a tourist site. We analyse video data from groups walking across unfamiliar moorland terrain, following a guide and map app which takes them on a tour of a remote Roman marching camp in the Brecon Beacons National Park, Wales. Following an ethnomethodological and conversation analytic approach, we examine three instances of navigational work for paired walkers as they traverse the moorland. The three fragments are of: an orientational struggle to establish where to go next; a routine check to select a path; and the discovery of a feature mentioned in the guide. Across the three episodes we explicate how our walkers make sense of the guide and map in relation to investigating the moorland surface. We examine how their ambulatory and undulatory practices on the moorland are tied to their wayfinding practices. While we analyse wayfinding talk, we also attend to the mobile practices of stopping and pausing as part of practical navigational reasoning. Abstract : This paper explores how the challenges of wayfinding with new mobile devices can inform the development of digital mapping tools for navigation through difficult terrain. We explore three instances of navigational work by pairs in moorland terrain, using the techniques of ethnomethodology and conversation analysis. We demonstrate how ambulatory and undulatory practices on the moorland are tied to wayfinding practices and practical navigational reasoning.